EU environmental law - Van Calster, Geert, 1970- (Elgar European law, 2017)
This highly accessible book gives readers a thorough and nuanced overview of European environmental law, covering on the basic framework and principles as well as substantive law. It provides much-needed insight into a crucial area of legal practice throughout the EU; at a time when environmental law in Member States is becoming ever less 'national' and EU regulation is growing in scope and importance. The book provides state-of-the-art insights into key pieces of legislation and topical developments in various areas of environmental regulation. The first part offers a succinct overview of the framework of European environmental law and the fundamental principles that govern it. This part covers the creation, implementation and enforcement of environmental regulations and includes dedicated chapters on in particular environmental impact assessment and environmental liability. The chapters in the second part offer in-depth analysis of the substantive law in key areas, including biodiversity, air quality, waste and chemicals regulation, and climate change. European environmental regulation is becoming more complex and interrelated, making it a crucial field of study for European law graduates and an area of increasing exposure to the legal profession and in industry. This much-needed book combines detailed legal analysis with a concise and accessible style, making it an ideal companion for students, academics and professionals alike.